PARCERIA PÚBLICO PRIVADO: UM ESTUDO SOBRE O USO DE MATERIAL APOSTILADO NA EDUCAÇÃO INFANTIL NO MUNICÍPIO DE IRATI - PR - CZEKALSKI, ELISANDRA APARECIDA (2019)
This research aims to present a study on the public-private partnership between a County Secretariat of Education, in this case represented by Irati County/PR and SEFE/OPET Publisher, for the acquisition of didactic material such as course books for basic education, more specifically, for kindergarten classes that are included in the County Centers of Early Childhood Education – CMEI's. This partnership occurs since 2001. The study was based on the approach of the policies cycle, which provided the elements for the analysis and comprehension of such partnerships, as well as made it possible to understand the context of influences, which fosters political space for this kind of partnerships in the legislations, and the way this cycle becomes effective in practice. The methodological procedures adopted during the research process were: bibliographic review, interviews and discussion with the bibliography that has been published in the recent years in the educational public policies field, namely: those that establish and/or provide partnerships between the public sector and the private sector, those that institute curriculum policies for early childhood, those that indicate the relationship between theory and practice in the pedagogical practice of teachers. Thereby the work is divided into three chapters. In the first chapter we discuss the first context of the policies cycle: the context of influence, in which we briefly present the means that the State building process has maintained a direct influence on the organization, the implementation and the dissemination of public-private partnerships. In the second chapter, we emphasize the second context: the context of text production, in which we briefly present the memory of childhood, whereas it is necessary to understand the historical and social path that leads us to see and to define the child nowadays. In the third chapter we highlight the third context of the policies cycle: the context of practice. At this moment we intend to present and discuss the field of public education in the explored county. In order to understand this process, we interview three distinct characters: firstly, the County Secretary of Education who worked at the time (2001-2004) of the acquisition of the course books (2001); the Secretary of the current government (2017-2020) to understand the reasons for the permanence of the partnership up to now; and the teachers of Maternal III (three to four-year-old children), who use the course books in the CMEI's. Lastly, the final considerations allowed us to verify the urgency to seriously discuss the curriculum for childhood education in the county public policies, with a solid and pertinent theoretical basis, so that the pedagogical work with the little ones is adequate, stablishing the respect for childhood and its peculiarities as the major premise. That the implementation of national, state and municipal laws and official documents do not guarantee the autonomy of educational institutions, causing a succession of inadequate conceptions of child and childhood. Precisely, the most impaired characters in this process are those who make education happen every day: the teachers, accompanied by the children, who receive an education which is not the one they would like to have, not even entitled, however, unfortunately, it is the one that is offered to them.